Advanced glycation end‐products increase lipocalin 2 expression in human oral epithelial cells. (13th March 2020) - Kido, Rie; Hiroshima, Yuka; Kido, Jun‐ichi; Ikuta, Takahisa; Sakamoto, Eijiro; Inagaki, Yuji; Naruishi, Koji; Yumoto, Hiromichi
Abstract: Background and objectives: Diabetes mellitus (DM), a risk factor of periodontal diseases, exacerbates the pathological condition of periodontitis. A major factor for DM complications is advanced glycation end‐products (AGEs) that accumulate in periodontal tissues and cause inflammatory events. Lipocalin 2 (LCN2) is an antimicrobial peptide and inflammation‐related factor, and LCN2 levels increase in DM. In this study, the effects of AGEs and lipopolysaccharide of Porphyromonas gingivalis ( P g ‐LPS) on LCN2 expression in human oral epithelial cells (TR146 cells) and the role of secreted LCN2 in periodontitis with DM were investigated. Material and methods: TR146 cells were cultured with AGEs (AGE2) and control BSA and cell viability was estimated, or with P g ‐LPS. Conditioned medium and cell lysates were prepared from cultures of epithelial cells and used for Western blotting and ELISA to analyze LCN2, RAGE, IL‐6, MAPK, and NF‐κB. RNA was isolated from AGE‐treated TR146 cells and differentiated HL‐60 (D‐HL‐60) cells and used for quantitative real‐time PCR to examine the expression of LCN2 and interleukin‐6 (IL‐6) mRNAs. RAGE‐ and LCN2‐siRNAs (siRAGE, siLCN2) were transfected into epithelial cells, and AGE‐induced LCN2 expression was investigated. D‐HL‐60 cells were co‐cultured with TR146 cells that were transfected with siLCN2 and treated with AGEs, and IL‐6 mRNA expression in D‐HL‐60 cells and cell migration was investigated. Results: AGEs increased the expression levels of LCN2 and IL‐6 in oral epithelial cells. siRAGE and a neutralizing antibody for RAGE inhibited AGE‐induced LCN2 expression. AGEs stimulated the phosphorylation of ERK, p38, and NF‐κB in epithelial cells, and their inhibitors suppressed AGE‐induced LCN2 expression. In contrast, P g ‐LPS did not show a significant increase in LCN2 level in TR146 cells that expressed Toll‐like receptor 2. In co‐culture experiments, AGE‐induced LCN2 inhibited IL‐6 mRNA expression in D‐HL‐60 cells, and LCN2 knockdown in epithelial cells suppressed HL‐60 cell migration. Conclusion: These results suggested that AGEs increase LCN2 expression via RAGE, MAPK, and NF‐κB signaling pathways in oral epithelial cells, and secreted LCN2 may influence the pathological condition of periodontitis with DM.